The Relationship between Obesity and Physical Activity of Children in the Spotlight of Their Parents' Excessive Body Weight - Sigmund, Erik; Sigmundová, Dagmar (International journal of environmental research and public health, 2020)
BACKGROUND: The study reveals the relationships between daily physical activity (PA) and the prevalence of obesity in family members separated according to the participation of their offspring in organized leisure-time physical activity (OLTPA), and answers the question of whether the participation of children in OLTPA is associated with a lower prevalence of obesity in offspring with respect to parental PA and body weight level. METHODS: The cross-sectional study included 1493 parent-child dyads (915/578 mother/father-child aged 4-16 years) from Czechia selected by two-stage stratified random sampling with complete data on body weight status and weekly PA gathered over a regular school week between 2013 and 2019. RESULTS: The children who participated in OLTPA ≥ three times a week had a significantly lower (p < 0.005) prevalence of obesity than the children without participation in OLTPA (5.0% vs. 11.1%). Even in the case of overweight/obese mothers/fathers, the children with OLTPA ≥ three times a week had a significantly lower (p < 0.002) prevalence of obesity than the children without OLTPA (6.7%/4.2% vs. 14.9%/10.7%). CONCLUSIONS: The cumulative effect of regular participation in OLTPA and a child's own PA is a stronger alleviator of children's obesity than their parents' risk of overweight/obesity.
Keywords: Female; Overweight; dítě; předškolní dítě; ženské pohlaví; vztahy mezi rodiči a dětmi; průřezové studie; Adolescent; Obesity; lidé; cvičení; tělesná hmotnost; Cross-Sectional Studies; obezita; Male; Czech Republic; Parent-Child Relations; Child, Preschool; rodinné vztahy; nadváha; index tělesné hmotnosti; Family Relations; Body Weight; Česká republika; Child; mužské pohlaví; Body Mass Index; Exercise; mladiství; Humans